To the problem of conflicts in the field of aviation - Череватюк, В. Б. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In this article discussion lies in the question about separate kinds, warning technologies and methods of decision of conflicts in the sphere of aviation. It was proved that basic efforts must be directed on the conflict-free resolution of problems which arise up as a result of objective contradictions. The main directions of warning and decision of conflicts must lean against improved normatively legal basis and principles of democratic development of the world.